Clinical, cytologic, and immunohistochemical features of sarcomas involving body cavity fluids. Issue 12 (6th November 2019) - Chen, Athena L.; Janko, Elizabeth; Pitman, Martha B.; Chebib, Ivan
Abstract : Background: Sarcomas are uncommon findings in body cavity fluids. Diagnosis may be challenging because sarcoma cells in fluids can round up and lose their characteristic appearance seen on smears and histologic sections. This study characterizes the cytologic features of sarcomas involving body cavity fluids. Methods: Effusion fluids and cerebrospinal fluids diagnosed as positive for sarcoma were reviewed. Results: Forty‐three fluids from 28 patients (median age, 47 years) were positive for sarcoma. Four patients who presented with positive fluids were alive at 1 to 10.7 years' follow‐up (median, 22.5 months). Twenty‐four patients died 2 days to 2 years (median, 19 days) after their positive fluid diagnoses. Twenty‐eight specimens from 20 patients had slides available for review. Although 18 of the 28 positive fluids had a morphology comparable to that of their primary, 4 small round blue cell tumors (SRBCTs) and 4 spindle cell tumors showed epithelioid morphology, 1 SRBCT had pleomorphic morphology, and 1 epithelioid primary had SRBCT morphology. Nine fluids had tumor cells in large, cohesive clusters mimicking carcinoma; workup was performed for 10, predominantly to rule out carcinoma and mesothelioma. Conclusions: Sarcoma morphology may be altered in exfoliated cytology specimens. Workup on cell blocks aids in the differential diagnosis, especially for carcinoma and mesothelioma. Unsurprisingly, fluid cytology positive for sarcoma portends poor survival. Abstract : Sarcoma morphology may be altered in exfoliated cytology specimens, most frequently to epithelioid morphology. Unsurprisingly, fluid cytology positive for sarcoma portends poor survival.